WATER QUALITY ASSESSMENT AND STATUS OF PHYTO- AND ZOO PLANKTON OF HIMALAYAN BHAGIRATHI RIVER IN UTTARKASHI, UTTARAKHAND (INDIA) (Applied Biological Research, 2024)
Rivers are important source of fresh water which is important for the sustenance and   welfare of the society. The present study deals with the assessment of water quality   parameters and with the population of phyto- and zoo-plankton of Himalayan  Bhagirathi river in Uttarkashi, Uttarakhand (India). The samples were collected   from the study area during summer, monsoon, and winter seasons for water   quality and phyto- and zoo-plankton analysis. The air temperature, depth  temperature, pH, total alkalinity, total dissolved solids (TDS), dissolved oxygen   (DO), turbidity, free CO2, electric conductivity (EC), biological oxygen demand   (BOD) and total hardness were determined. The study revealed that DO was   maximum in winter (12.35 ± 0.25 mg L-1) and minimum in June to September   (9.75 ± 0.25 mg L-1). The Bhagirathi water contained maximum DO in colder   month, followed by a gradual decrease to its lowest value during June to   September. BOD, an important indicator of pollution status of a water body, was   high during summer perhaps due to low discharge at river. BOD was high in   monsoon (4.4 ± 0.14 mg L-1) and low in winter (1.5 ± 0.14 mg L-1). The study   revealed low river flow during winter. Bacillariophyceae was maximum (442   units L-1) in February and minimum (18 units L-1) in July. Chlorophyceae was   maximum (80 units L-1) in January and minimum (6 units L-1) in August, while   Myxophyceaewas maximum (34 units L-1) in February and minimum in June   and Xanthophyceae was not recorded at this site. The maximum number of   zooplankton genera was observed during winter and minimum in rainy season.   The study showed that there is an urgent need to have proper water management   in rainy and summer seasons so as to restore the water quality of this river.
Keywords: Himalayan ecosystem; phytoplankton; river health; water quality; zooplankton